Gynura procumbens leaf extract-loaded self-microemulsifying drug delivery system offers enhanced protective effects in the hepatorenal organs of the experimental rats - Manik Chandra Shill; Md. Faisal Bin Jalal; Madhabi Lata Shuma; Patricia Prova Mollick; Md. Abdul Muhit; Shimul Halder (PLoS ONE, 2025)
Gynura procumbens, known as longevity spinach, is a plant traditionally used in tropical Asian countries for its anti-inflammatory, hepatoprotective, anti-hypertensive, and anti-hyperglycemic properties. The current study aimed to enhance the hepatorenal protective activity of Gynura procumbens leaf extract (GLE) by developing a self-microemulsifying drug delivery system (SMEDDS). SMEDDS-GLE exhibited the formation of small micelles with a mean droplet size of 231 nm. This resulted in a significant enhancement in the dispersion of GLE in water, as evidenced by a dispersibility that was at least 4.8 times greater than that of GLE alone. In the rat model of hepatic injury induced by cisplatin (7.5 mg/kg, i.p.), the administration of SMEDDS-GLE (75 mg-GLE/kg, p.o.) significantly reduced liver damage, observed by histological examination and reduced levels of plasma biomarkers associated with hepatic injury. Furthermore, according to histological examination findings and plasma biomarkers assessment, SMEDDS-GLE enhanced the nephroprotective benefits of GLE in the rat model of acute kidney injury. Based on these findings, a strategic application of the SMEDDS-based approach could be a viable choice to enhance GLE’s nutraceutical properties.